Use of isoperibolic reaction calorimeter for the study of reaction kinetics of acetic anhydride hydrolysis reaction: effect of acetic anhydride and water ratio - Kumar, Rajendra; Tiwari, Anurag Kumar (Chemical and Process Engineering-Inzynieria Chemiczna I Procesowa, 2022)
Reaction kinetics of acetic anhydride hydrolysis reaction is being studied at a fixed reaction temperature and ambient pressure using an isoperibolic reaction calorimeter. Temperature versus time data along with heat and mass balance is used to determine the kinetics parameters i.e. activation energy and Arrhenius coefficient. It has been studied with the varying volumetric ratio of acetic anhydride and water; and kinetics parameters were compared and plotted for each ratio. Such a study has not been done previously to determine the kinetics dependency on varying the acetic anhydride water ratio. As the acetic anhydride hydrolysis reaction is exothermic in nature, the present study will help to decide the safe and suitable operating conditions such as concentration and temperature for conducting this reaction at plant scale. The kinetic data presented can be used further for the mathematical modeling and simulation of such exothermic hydrolysis reactions.
Keywords: acetic anhydride; Hydrolysis; kinetics; reaction calorimeter; Water